The Medieval Background of papal Primat and Infallibilitas or rather their political Meaning Hic et Nunc - XU, Longfei (Journal of Research for Christianity in China (JRCC), 2023)
This article has his main theme not only about the papal Primacy and Infallibility, but also on their political meaning contemporary; After the orientation of methodic it discusses at first mainly the medieval background even to the 19. Centry, and then the question about the reference of the church- and profane history, multy strained moments of inner-church- and profane political structure, Pope and his reform, investitur, schism of Pope etc. at the end is conclusion on the contemporary meaning of the discussed question in several aspects.
Keywords: Pope, Primacy, infallibility, church-reform, investitur